VISUAL CLIP IN EDUCATION IN PRIMARY SCHOOL - TVARUZKA, Vaclav (Trends in education, 2010)
The paper is dedicated to preferences of teachers that use educational clip during education of pupils in primary school. The paper is about research that was done for this topic and also about connections that follow from this research. The research of this problem enables to follow values that are possible to quantify.
Keywords: Visual educational clip; image-based research; visual research; conceptual knowlege; primary school pupil.